Infrared-active quadruple contrast FePt nanoparticles for multiple scale molecular imaging. (April 2016) - Chou, Shang-Wei; Liu, Chien-Liang; Liu, Tzu-Ming; Shen, Yu-Fang; Kuo, Lun-Chang; Wu, Cheng-Ham; Hsieh, Tsung-Yuan; Wu, Pei-Chun; Tsai, Ming-Rung; Yang, Che-Chang; Chang, Kai-Yao; Lu, Meng-Hua; et al.
Abstract: A single nanomaterial with multiple imaging contrasts and functions is highly desired for multiscale theragnosis. Herein, we demonstrate single 1–1.9 μm infrared-active FePt alloy nanoparticles (FePt NPs) offering unprecedented four-contrast-in-one molecular imaging – computed tomography (CT), magnetic resonance imaging (MRI), photoacoustic (PA) imaging, and high-order multiphoton luminescence (HOMPL) microscopy. The PA response of FePt NPs outperforms that of infrared-active gold nanorods by 3- to 5.6-fold under identical excitation fluence and particle concentrations. HOMPL (680 nm) of an isolated FePt NP renders spatial full-width-at-half-maximum values of 432 nm and 300 nm beyond the optical diffraction limit for 1230-nm and 920-nm excitation, respectively. The in vivo targeting function was successfully visualized using HOMPL, PA imaging, CT, and MRI, thereby validating FePt as a single nanomaterial system covering up to four types (Optical/PA/CT/MRI) of molecular imaging contrast, ranging from the microscopic level to whole-body scale investigation.